2018
DOI: 10.1111/eje.12383
|View full text |Cite
|
Sign up to set email alerts
|

Investigating an errorless learning approach for developing dental operative technique skills: A pilot study

Abstract: These preliminary findings suggest handpiece skills can be acquired implicitly via errorless learning, and it is less attentionally demanding than errorful learning, as evident by maintenance of preparation performance when processing additional relevant instructions and multitasking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The efficacy of these various approaches for learning motor skills has been demonstrated in dentistry. For example, in restorative dentistry, using a procedure to reduce the production of errors (i.e., errorless learning: learning from simple to complex task), has been shown to result in significantly higher levels of performance during both learning and testing phases compared with learning explicitly via increasing errors (errorful: from complex to simple task) [6,13]. Errorless (implicit) learning is thought to result in motor skill performance that does not require working memory resources.…”
Section: Implicit and Explicit Learningmentioning
confidence: 99%
See 3 more Smart Citations
“…The efficacy of these various approaches for learning motor skills has been demonstrated in dentistry. For example, in restorative dentistry, using a procedure to reduce the production of errors (i.e., errorless learning: learning from simple to complex task), has been shown to result in significantly higher levels of performance during both learning and testing phases compared with learning explicitly via increasing errors (errorful: from complex to simple task) [6,13]. Errorless (implicit) learning is thought to result in motor skill performance that does not require working memory resources.…”
Section: Implicit and Explicit Learningmentioning
confidence: 99%
“…Indeed, a core principle of implicit learning approaches is to develop learning protocols that minimize hypothesis testing and prevent participants learning from their errors [64]. Despite the increasing body of evidence supporting implicit approaches of motor task learning, most of these studies were related to simple gross motor learning (e.g., sports) [7,57,64] compared to a limited number of studies addressing complex fine motor tasks used in medicine and dentistry [6,13].…”
Section: Implicit and Explicit Learningmentioning
confidence: 99%
See 2 more Smart Citations
“…It is indeed reported that insufficient incisal reduction is one of the most frequent problems encountered during training (Christensen, 2007;Syed, Al-Moaleem, & Shariff, 2016). A recent strategy to improve quality of training proposes to concentrate on individual tasks, during initial learning, in order to reduce attention demands and increase knowledge recall (Winning, Malhotra, & Masters, 2018).…”
Section: Introductionmentioning
confidence: 99%